ANALISIS PERBANDINGAN PROFITABILITAS SEBELUM PANDEMI DAN PADA MASA PANDEMI COVID-19 PADA SEKTOR CONSUMER CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA (2018-2021) - Meivi Herlina Siwu; Victorina Z. Tirayoh (Universitas Sam Ratulangi, 2022)
The profitability ratio is a ratio used to determine the company's ability to generate profits. During this pandemic, it is essential to know the company's financial condition to make decisions. This study aims to determine significant differences in profitability ratios before the pandemic and during the Covid-19 pandemic in the Consumer Cyclicals Sector listed on the Indonesia Stock Exchange. The research method used in this study is comparative quantitative, using 62 companies for a comparison of two years before (2018-2019) and two years during the Covid-19 pandemic (2020-2021). TheÂ data analysis used was the Wilcoxon Signed Rank Test.Â The research results show significant differences in profitability ratios, that is, net profit margin, return on assets, and return on equity before the pandemic and during the Covid-19 pandemic in the Consumer Cyclicals Sector Listed on the Indonesia Stock Exchange.